Influence of cross-cultural management on the development of tourism: example of Pozega-Slavonia county - Mihaela Markovac (Vallis Aurea, 2018)
This paper analyses the influence of cross-cultural management on the development of tourism, with the emphasis on Požega-Slavonia County. Management is an integral part of modern business and governance of resources. However, global market requires distinctiveness, something that differentiates a product or service from the competition. That is why cross-cultural management is gaining significance in modern business, since it is putting culture and tradition in the function of business and realising its potential primarily in tourism. By acknowledging cultural differences, cross-cultural management adapts those same differences to the needs of business. Here it is important to know how to present and direct the richness of culture and tradition and make it sustainable. The example of Požega-Slavonia County (which is at the very bottom in Croatia in terms of development) points to the insufficient utilisation of possibilities that the cross-cultural management offers. The causes of this underdevelopment, despite a rich culture and tradition of Požega-Slavonia County, are truly numerous. But, with a well-thought-out strategy of cross-cultural management, the tourism in Pozega-Slavonia County should become the key aspect in recognising this area as a place of oeno-gastro experience.